Issues of arbitration proceedings about indemnity damages from emergencies in Arctic region states - Gavrilenko Vladimir (Saint-Petersburg University of State Fire Service of EMERCOM of Russia, 2021)
This article research the legislation of the Arctic region states, regulating institution of commercial arbitration and issues of arbitration proceedings about disputes on compensation for damage from emergency situations. The author speaks about legal regulation of this issue and formulates conclusions about the main problems and shortcomings of legal acts in this area.